2014
DOI: 10.1016/j.neuroscience.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency induces anorexia by inhibiting hypothalamic AMPK

Abstract: Obesity and eating disorders are prevailing health concerns worldwide. It is important to understand the regulation of food intake and energy metabolism. Thiamine (vitamin B1) is an essential nutrient. Thiamine deficiency (TD) can cause a number of disorders in humans, such as Beriberi and Wernicke-Korsakoff syndrome. We demonstrated here that TD caused anorexia in C57BL/6 mice. After feeding a TD diet for 16 days, the mice displayed a significant decrease in food intake and an increase in resting energy expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 47 publications
5
30
1
Order By: Relevance
“…C57Bl/6 mice fed a thiamine deficient diet for 16 days showed severe (17–24%) weight loss related to significant decreases in food intake and increases in resting energy expenditure; experiments suggested that thiamine deficiency may inhibit a critical regulator of food intake, hypothalamic adenosine monophosphate-activated protein kinase (AMPK) (Liu et al, 2014). Thiamine deficiency also resulted in changes to physiology and behavior including piloerection, splayed legs, gait problems, loss of trunk tone, and loss of righting reflex.…”
Section: Discussionmentioning
confidence: 99%
“…C57Bl/6 mice fed a thiamine deficient diet for 16 days showed severe (17–24%) weight loss related to significant decreases in food intake and increases in resting energy expenditure; experiments suggested that thiamine deficiency may inhibit a critical regulator of food intake, hypothalamic adenosine monophosphate-activated protein kinase (AMPK) (Liu et al, 2014). Thiamine deficiency also resulted in changes to physiology and behavior including piloerection, splayed legs, gait problems, loss of trunk tone, and loss of righting reflex.…”
Section: Discussionmentioning
confidence: 99%
“…It has now been established that TD is the primary cause of WKS. Clinically, WKS is usually associated with chronic alcoholism which depletes thiamine in the human body, but it can also be caused by malnourishment [43, 44]. …”
Section: Td and Neurodegenerationmentioning
confidence: 99%
“…This mechanism is common to several orexigenic signals, such as hypoglycaemia, ghrelin, glucocorticoids, adiponectin, and cannabinoids [117,[119][120][121][122][123][124][125] . Some anorexigenic signals, such as leptin, insulin, GLP-1, ciliary neurotrophic factor, thiamine deficiency, and melanocortin receptor agonists, also exert their effects inhibiting hypothalamic AMPK [117,118,120,[126][127][128][129][130][131][132] ( Fig. 1 ).…”
Section: From Hypothalamic Lipid Metabolism To Whole Body Energy Homementioning
confidence: 99%
“…Interestingly, leptin action is also mediated by the AMPK inhibition that occurs in the ARC, VMH, and PVH, where, as a result of that action, the concentration of palmitoyl-CoA is increased [118,128,133] . In this regard, the role of AMPK in the PVH has been investigated thoroughly, demonstrating that, besides leptin, AMPK is modulated in similarity to other nuclei by hypoglycaemia and thiamine [132,134] but not by ciliary neurotrophic factor [127] , demonstrating anatomical specificity. Finally, it has also been proposed that AMPK in vasopressin neurons of the PVH may be involved in adiponectin effects on osmoregulation [135] .…”
Section: From Hypothalamic Lipid Metabolism To Whole Body Energy Homementioning
confidence: 99%